Perancangan Jaringan Voice Over Internet Protokol (Voip) Menggunakan Platform Asterisknow - Ahmad Fauzi; Ade Setiawan; Dwi Yuni Utami (Computer Science (CO-SCIENCE), 2022)
Communication is an important stage to support the running of a work program, without good communication it can cause misunderstandings between the two parties, the importance of the role of communication means several companies are growing rapidly in order to innovate in the manufacture of equipment in the telecommunications sector, which is commonly used in long-distance communication. far is the use of telephone services, both individual telephones and company-based telephones, for some companies that use high-enough telephone activity, this will result in soaring telephone bills that must be paid, thus to reduce the level of communication with high costs, we can use VoIP technology ( Voice Over Internet Protocol) which can be used by utilizing the TCP / IP protocol where the protocol without us realizing it is a protocol used for exchanging data, thus the protocol can also be accessed. used as voice voice data exchange using Open Source Software in the Asterisk application which is used as a substitute for PBX (Private Branch Exchange) devices, where in the application it is used to make the TCP / IP protocol as an intermediary for data exchange to communicate or Voice. The advantage of this application is that it is able to serve a maximum of 1000 online accounts on one server and 240 concurrent calls. This is of course suitable for companies who want to implement this technology based on open source applications.